REVEALING TIMBER STRUCTURES POTENTIAL IN DECARBONIZATION OF LOW-RISE RESIDENTIAL BUILDINGS (Collection of scientific works «Modern structures of metal and wood», 2023)
The article presents the results of theoretical studies on embodied carbon for load-bearing wall structures prevailing in low-rise buildings consturction practice in order to reveal the potential  of  timber  structures  in  decarbonization  of  the  construction  sector.  Seven  types  of  wall structures were considered in the study. CO 2  emissions were determined using the environmental product  declarations  for  relevant  materials  considering  sequential  life-cycle  stages  (raw  material supply,  production  and  transportation  of  building  products,  construction  process,  building  waste transportation  and  disposal)  with  regard  to  recycling  benefits.  A  lightweight  timber  framed  wall panel was shown to have minimum carbon emissions at each life-cycle stage leading to lowest total carbon embodied.